Physico-chemical Analysis, Total Polyphenolic Content and Antioxidant Capacity of Yellow Dye Extracted from Curcuma longa: Antioxidant Capacity of Yellow Dye (Biological Sciences - PJSIR, 2021)
Turmeric (Curcuma longa) is a well known condiment of the Asian cuisine and also used as ayurvedic medicine in the content, since ancient times due to its potential therapeutic properties. Main colouring constituent of Curcuma longa is curcumin and curcuminoids. In the present work natural yellow dye was extracted from rhizome of turmeric using an effective low cost method of solvent extraction. The developed natural yellow dye was assessed for physico-chemical analysis, toxicity, polyphenolic content and antioxidant activity. Physico-chemical assay showed good nutritional profile of the extracted natural yellow dye and quite safe at dose level 3.5g/Kg body wt. Significant phenolic content was found to be 63.32 mg GAE/100g, and also showed potent antioxidant capacity (% inhibition) ranging from 5.1-20.4 at 1-5 mg/mL concentration. Animal trials showed no mortality in the mice.